‘Me juzgo por natural de Madrid’: Vincencio Carducho, theorist and painter of Spain's court capital - Bass, Laura J.; Andrews, Jean (Taylor and Francis, 2016)
More than a guide for painters, Vicente de Carducho's Diálogos de la pintura has long been recognized to promote painting as a liberal art and to advocate for the creation of an academy of painting in seventeenth-century Madrid. But questions of patriotic belonging and prestige are also at stake in this erudite treatise. In his prologue, Carducho prioritizes his allegiance to his adopted city even while acknowledging his debts to his native Florence. The first part of this article argues that the treatise serves to showcase that allegiance as it participates in a project to make the young political capital a great cultural centre. The second part makes the case for Carducho as a practitioner who understood the debt he owed to the visual culture of his adopted homeland while remaining true to the aesthetic principles of his Florentine training. His late depictions of saints in adoration of the crucifix provide a focus for examining a religious sensibility subtly informed by Spanish devotional literature.